A REVIEW OF PARTICULATE FILLERS IN UNSATURATED POLYESTER COMPOSITES: PROPERTY ENHANCEMENT AND APPLICATIONS: THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
In this study, a review of mechanical properties of unsaturated polyester reinforced by particle composite material has been investigated. The review study involved the compression, tensile, impact, fatigue properties of polyester reinforced by alumina particles Al2O3. This review presents a comprehensive overview of recent advancements in unsaturated polyester composites reinforced with various particulate materials. The methodology relies on compiling and analyzing the results of several studies that used different proportions of particulate fillers within the polymer matrix. The results showed that the addition of Al₂O₃ particles significantly affects the mechanical properties, improving tensile and fatigue strength at certain filler ratios. However, above a certain concentration, compressive or impact resistance may be reduced due to weak interfacial bonding or particle agglomeration. It was also demonstrated that particle distribution, size, and addition ratio play a key role in determining the mechanical performance of composite materials. It explores the influence of different types of particles (e.g., natural fillers, mineral fillers, synthetic fillers) on the resulting composites' mechanical, thermal, and physical characteristics. Furthermore, the review examines the processing techniques employed for fabricating these composites and highlights the applications of particle-reinforced UPRs across diverse industries, including construction, automotive, and marine sectors. At last, the review identifies current defy and future perspectives in developing and use of unsaturated polyester-based particle composite materials.